The Influence of Average Dividend Yield, Inflation Rate and Unemployment Rate on The Profitability Of Office-Based Malaysian Real Estate Investment Trusts (M-Reits) - Min, Voong Wee; Salawati, Sahari; Sritharan, Nivakan; Sharon, Cheuk Choy Sheung (2022)
One of the obstinate problems in the studies of Real Estate Investment Trusts (REITs) is the difficulty in identifying the factors that determine the performance of REITs. Studies in the literature have so far developed various approaches to measure the performance of REITs, however, an exhaustive review of literature suggest the use of profitability to measure the performance of REITs. Though office-based REITs increasingly important in Malaysia, inferior number of studies made an attempt to investigate the performance. To fill the gap, this seminal article intends to investigate the relationship between the factors, such as average dividend yield, inflation rate, and unemployment rate, and the profitability of Malaysian office-based REITs using tax-adjusted value weighted index (TAVWI). To do so, this study unpacked 11 listed Malaysian office-based REITs to compute the TAVWI for the period starting from 1990 to 2019 with 30 observations. In doing so, descriptive analysis and multiple regression were employed to analyse the collected data. The insights reveal that profitability of Malaysian REITs is impacted negatively by dividend yield, while not by inflation rate and unemployment rate. As a whole, this article should be a useful resource for gaining fresh insights about the performance of office-based REITs in Malaysia.